A psychometric validation of the Japanese versions of new questionnaires on tinnitus (THI-12, TRS, TRSw, TSS, and TSSw). (May 2013) - Wasano, Koichiro; Kanzaki, Sho; Sakashita, Tetsushi; Takahashi, Mariko; Inoue, Yasuhiro; Saito, Hideyuki; Fujioka, Masato; Watabe, Takahisa; Watanabe, Reiko; Sunami, Kishiko; Kato, Shoko; Kabaya, Kayoko; et al.
Abstract Conclusion: The Japanese version of the Tinnitus Handicap Inventory-12 (THI-12), Tinnitus Rating Scale (TRS), TRS 1-week version (TRSw), Tinnitus Severity Scale (TSS), and TSS 1-week version (TSSw), which were developed in this study, showed high reliability and validity, suggesting their usefulness in clinical practice. Based on the THI severity grades, we propose that the severity grades of THI-12 (draft) are categorized into four groups: 0–4 points, 5–9 points, 10–14 points, and 15–24 points. Objectives: We developed Japanese versions of new questionnaires for evaluating the level of psychological distress and difficulty in activities of daily living due to tinnitus, and performed their psychometric validation to determine the reliability and validity. The THI-12 is an assessment consisting of 12 items, each of which is rated on a 3-point scale that was created by reducing the number of questions from the 25 items of the THI. The TRS, TRSw, TSS, and TSSw, which were self-evaluation questionnaires of tinnitus on an 11-grade integer Likert scale from 0 to10 points, were used as additional instruments to assess tinnitus severity and distress. Methods: The subjects were healthy adults, and patients with subjective tinnitus who were examined at the Otolaryngology Department of Keio University Hospital, Osaka City University Hospital, or Nagoya City University Hospital with a chief complaint of tinnitus between September 2010 and January 2011. In all, 38 healthy adult subjects and 113 patients with subjective tinnitus were included. We examined the reproducibility and the internal consistency for reliability. We also examined the relationship with the available scales (THI and Hospital Anxiety and Depression Scale, HADS) and group divergence for validity. Results: The psychometric validation showed high reliability and validity of the THI-12, TRS, TRSw, TSS, and TSSw.